Enhancing Student Learning Outcomes Through the Development of Interactive Flipbooks Using Heyzine - Akbar, Iqbal Pratama Fajar; Smaragdina, Azhar Ahmad; Gunawan, Agung Wahyu; Nasmansyah, Wiki; Sari, Agista Yuana; Fauziah, Nur; Wardhani, Eka Rachmawati (Universitas Negeri Malang, 2024)
This research aims to develop innovative informatics learning media that are relevant to the characteristics of students at SMP Negeri 16 Malang. The background of this research is based on the challenges faced in informatics learning, including low learning motivation and the lack of optimal technology utilization. Interactive flipbooks were chosen as the learning media due to their ability to integrate audio-visual elements and support independent learning. This research employs the Research and Development (R&D) method with the ADDIE model. The analysis stage identifies the needs, curriculum, and student characteristics. The design stage involves structuring the flipbook development framework. The development stage focuses on creating a web-based interactive flipbook and expert validation. The implementation stage is conducted with small and large groups to obtain feedback. The evaluation stage measures the effectiveness of the media and ensures its feasibility. The research results indicate that interactive flipbooks have the potential to increase learning motivation and understanding of informatics concepts.